2021
DOI: 10.21203/rs.3.rs-909572/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytomegalovirus Reactivation in Immunocompetent Mechanical Ventilation Patients: A Prospective Observational Study

Abstract: Background: Cytomegalovirus (CMV) reactivation is associated with adverse prognoses of critically ill patients. However, the epidemiology and predictors of CMV reactivation in immunocompetent patients receiving mechanical ventilation (MV) are not clear. The aim of this study was to investigate the epidemiology and predictors of CMV reactivation in immunocompetent patients requiring MV.Methods: A single-center, prospective observational study (conducted from June 30, 2017 to July 01, 2018) with a follow-up of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…They also reported an AUC for LUS score to predict weaning failure of 0.885 (95% CI 0.770-0.999, P < 0.001), and a cut-off score of 10 provided specificity of 72.7% and sensitivity of 92.3%. 25 These results also match with the results published previously which showed that despite similar basal LUS scores in patients with weaning failure (13 (10-17)) and weaning success (12 (8-15)), LUS scores significantly increased during the SBT in both groups. 9 Several studies reported similar cut-off values of ≤ 14 and <12 respectively as a predictor of weaning success.…”
Section: Discussionsupporting
confidence: 92%
“…They also reported an AUC for LUS score to predict weaning failure of 0.885 (95% CI 0.770-0.999, P < 0.001), and a cut-off score of 10 provided specificity of 72.7% and sensitivity of 92.3%. 25 These results also match with the results published previously which showed that despite similar basal LUS scores in patients with weaning failure (13 (10-17)) and weaning success (12 (8-15)), LUS scores significantly increased during the SBT in both groups. 9 Several studies reported similar cut-off values of ≤ 14 and <12 respectively as a predictor of weaning success.…”
Section: Discussionsupporting
confidence: 92%